A non-nuclear inline densitometer for multiphase flows. (1st July 2023) - Ramakrishnan, Vijay; Arsalan, Muhammad; Deffenbaugh, Max
Abstract: Multiphase flowmeters are used in the oil-and-gas industry to measure real-time flow rates of oil, gas, and brine, flowing simultaneously as a non-homogeneous mixture, in a pipeline from wellhead to separator. Since these flow rates cannot be measured directly, they are inferred from other measurements including mixture density. Mixture density is commonly measured using nuclear densitometers which can be problematic in terms of safety and maintenance. This paper details the development—concept and experimental validation—of a non-nuclear inline densitometer that measures multiphase mixture density using pressure sensors. A comprehensive flow-loop test was conducted at a commercial facility to evaluate the technology under a wide range of flow conditions—flow rates 1000 to 10000 bpd, gas fractions 0% to 96%, water cuts 0% to 100%, with a synthetic oil as liquid hydrocarbon, methane as gas medium, two water salinities—totaling nearly 300 test points. The results from this experimental validation—specifically, the technology's accuracy and operating envelope—point to a groundbreaking practical solution to a long-standing problem.